The Use of Gadgets in Early Childhood: A Literature Review of Benefits and Risks - Nila Puspitasari, Ratna (Journal of Early Childhood Education Research, 2025)
Purpose: The rapid proliferation of digital technology has fundamentally transformed early childhood education, with gadgets such as smartphones, tablets, and computers becoming increasingly integrated into young children's daily routines. While controlled gadget use demonstrates potential to enhance cognitive, language, and motor development, growing evidence indicates that excessive screen time poses significant risks to social development, sleep quality, and physical health. This literature review examines the dual nature of gadget use in early childhood, aiming to synthesize current evidence on both educational benefits and developmental risks. The study's significance lies in providing comprehensive, evidence-based guidance for stakeholders to navigate the complex landscape of digital technology in early learning environments. Methodology: This study employed a systematic literature review approach, analyzing peer-reviewed research published between 2015 and 2024. Data sources included major academic databases such as Scopus, Web of Science, ERIC, and PubMed. The review synthesized findings from empirical studies examining gadget use among children aged 0-8 years, focusing on educational outcomes, developmental impacts, and screen time management strategies. Thematic analysis was utilized to identify patterns across studies regarding benefits, risks, and effective practices in digital technology integration within early childhood education contexts. Results: The analysis reveals that controlled, educationally oriented gadget use can support skill development in specific domains including literacy, numeracy, and problem-solving when integrated with adult guidance and age-appropriate content. However, excessive unsupervised screen time consistently demonstrates negative associations with language acquisition, attention span, social-emotional competence, sleep duration and quality, and physical activity levels. Children exposed to prolonged screen time without parental mediation show increased risk of encountering inappropriate content, developing problematic usage patterns, and experiencing delays in social skill development. Optimal outcomes occur when screen time is limited, purposeful, co-engaged with caregivers, and balanced with hands-on play and social interaction. Conclusions: This review establishes that gadget use in early childhood presents both opportunities and challenges requiring careful navigation. Effective integration of digital technology in early learning depends critically on establishing clear usage guidelines, ensuring active parental and educator involvement, prioritizing high-quality educational content, and maintaining balance with traditional play-based learning. The findings provide actionable recommendations for parents, educators, and policymakers to develop frameworks supporting beneficial gadget use while mitigating developmental risks, ultimately fostering healthy, technology-enriched learning environments that support children's holistic development in the digital age.